Vertical jumping power normative-reference values: Utilizing a large cohort of Canadian University students - Morassutti Olivia N.; van Wyk Paula M.; Duquette Adriana M. (Biomedical Human Kinetics)
Study aim: This study aimed to develop vertical jumping power normative-reference standards based on a large cohort of Canadian university students.